Psychosocial Correlates of Frailty in Older Adults - Freitag, Simone; Schmidt, Silke (My University, 2016)
Background: The aim of this study was to investigate psychosocial variables associated with frailty status. Moreover, gender differences in the psychosocial variables associated with frailty were examined. Methods: This cross-sectional study examined a community-dwelling sample of N = 210 older adults (M = 75.31 years). Frailty was measured with the Tilburg Frailty Indicator. Quality of life, depression, resilience, social support, self-efficacy, traumata experienced, and trauma severity were assessed as psychosocial variables. Logistic regression analyses were performed. Results: In total, 41.4% of the participants were frail (49.6% women, 27.8% men). Main correlates of frailty were depressive symptoms, quality of life, and resilience. Gender differences for frailty correlates were found. Depressive symptoms and perceived social support were mainly associated with frailty in women. Furthermore, age was only significantly associated with frailty in women. Quality of life was significantly associated with frailty being a protective factor in both women and men. Trauma count and trauma severity were associated with an elevated risk for frailty in men. Conclusions: The results show that the psychosocial variables depressive symptoms, quality of life, and resilience are associated with frailty. Gender-specific differences in psychosocial correlates of frailty were revealed. Results suggest that gender-specific assessments and interventions should be developed to prevent frailty in late life.
Keywords: Alter; Geschlechterdifferenz; Depression; Lebensbedingungen; 610 Medizin und Gesundheit